Masa Depan Pemasyarakatan: Inovasi dan Transformasi Untuk Meningkatkan Kualitas Hidup Narapidana - Marliyoda Aji Pangestu; Ali Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The future of corrections offers the potential for significant innovation and transformation in efforts to improve the quality of life for inmates. With technological developments and a more holistic approach to rehabilitation, correctional systems can become more effective in preparing prisoners for reintegration into society. Innovations in education, job training, mental health, and substance rehabilitation programs are key to ensuring that inmates have a better chance of success after release. A transformation in prison culture and management that focuses more on recovery rather than punishment can help reduce recidivism rates. Therefore, the future of correctional institutions must be based on the principles of rehabilitation and reintegration, with an emphasis on real efforts to improve the quality of life of prisoners for their welfare and that of society as a whole.